DETECTION OF GRAPEVINE FANLEAF VIRUS BY NEW GRNAS (Experimental biology, 2025)
Grapevine fanleaf virus (GFLV) is an important worldwide pathogen of grapes that leads to significant economic losses due to reduced health and productivity of the vines. In this study, a highly sensitive and specific molecular diagnostic system for GFLV was established. Synthetic control sequences were developed to detect conserved regions of the viral RNA2 genome, enabling precise detection. The performance of a CRISPR/Cas12a-based diagnostic platform integrated with Recombinase Polymerase Amplification (RPA) was validated, demonstrating sensitive and rapid detection of GFLV even at low viral loads. Although the Cas13a system was tested, its sensitivity was insufficient due to guide RNA inefficiencies and the complex structure of viral RNA, indicating the necessity for further optimization. The combination of Cas12a with RPA was demonstrated to be a powerful diagnostic approach for the detection of plant viruses, with potential for field-integrated diagnostic applications. This research provides a foundation for the development of diagnostic tools aimed at controlling GFLV and improving viticulture management approaches, thereby promoting sustainable viticulture.
Keywords: grapevine fanleaf virus, CRISPR/Cas12a, recombinase polymerase amplification, molecular diagnostics, plant virus detection.